FAKTOR-FAKTOR PENYEBAB TERJADINYA KEKERASAN MAHASISWA PENDATANG DENGAN PENDUDUK LOKAL ( STUDI KASUS KEKERASAN MAHASISWA NTT DENGAN MASYARAKAT TAMBAKBAYAN, YOGYAKARTA ) - , Zaenal Abidin; , Dr Eric Hiariej M. Phil., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Existing diversity in one place, whether it is the diversity of cultures, religions and races making this region using multiculturalism as a reference to set the diversity in order to avoid conflicts that led to the violence. In addition to preventing the existing diversity of territory, multiculturalism is also expected to be able to bridge their peoples in addressing within cultures welcomed into daerahanya, so it has an agreed value system to maintain the integrity of each culture embraced by each member community without having to look at the differences that can lead to a dispute. Multiculturalism is also a tool to be used in response to cultute shock experienced by both their peoples to enter into the local culture as well as to other people of different cultures into their area, so that the regularity of the culture when one enters into this diverse region. because every culture has a different point of view, in making and looking at a life, so there is rarely any strengthening of ethnocentrism that each culture to other cultures and lead to stereotypes that would make the uniqueness of this diversity leads to the reinforcement of the action of each and the absence of a culture of tolerance and negotiation values are used as a tool to get them to know and appreciate their culture beyond which significantly different from the culture that they have. With the high multiculturalism can same in diversity and provide equal rights to something different and shy away from a dispute that caused by a difference. In this study, researchers found a strong ethnocentrism of each ethnic group so that when one member of the ethnic group or culture clash Culture shock caused many conflicts that led to the violence, it is also caused local residents Tambakbayan who does not have a value system that is offered to the public civil ethnicity that comes region so intertwined a communication between the two ethnic and the existence of a desire to get to know each ethnic group who are outside them. Inter-ethnic conflicts in the region rarely occurs among students with around but with the existence of a system of communication that happens people can be a mediator to deal with the problems of ethnic conflicts that occur territory, as well as disputes between the ethnic student population, it can serve as a mediator is another ethnic beyond the rival. In other words, the existence of a communication that exists between them can be used as a bridge between cultures beyond fatherly know their culture, so as to create a high tolerance when they are in a place and also as an agreed value system to be used as a tool to realize the potential diversity without conflict.